Generalization of (Q,L)-Fuzzy Soft Subhemirings of a Hemiring - K. Geetha; N. Anitha; S. Noeiaghdam; U. Fernandez-Gamiz; S.S. Santra; K.M. Khedher (Advances in Fuzzy Systems)
This paper investigates the properties and results of (Q,L)-fuzzy soft subhemirings ((Q,L)-FSSHR) of a hemiring R. The motivation behind this study is to utilize the concept of L-fuzzy soft set of a hemiring and to derive a few specific outcomes on (Q, L)-FSSHR. The concepts of strongest Q-fuzzy soft set relation, Q-isomorphism, pseudo-Q-fuzzy soft coset, and some of their related properties are implemented while analyzing the results. Finally, the properties are verified with a numerical example from the 2000 AMS subject classification: 05C38, 05A15, and 15A18.